2016
DOI: 10.1159/000443419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Peritoneal Low-Molecular-Weight-Protein-Removal in CCPD and CAPD Patients Based on C-Terminal Agrin Fragment Clearance

Abstract: Background/Aims: This study compares the peritoneal elimination of the low-molecular-weight-protein (LMWP) C-terminal agrin fragment (tCAF, size 22 kDa), a promising biomarker for kidney function, in continuous cycling peritoneal dialysis (CCPD) and continuous ambulatory peritoneal dialysis (CAPD). Methods: 103 sets of serum, 24h-urine and dialysate samples were obtained in 15 CCPD (63 sets) and 11 CAPD (40 sets) patients. Total, renal and peritoneal substrate removals/clearances were measured/calculated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Four papers were identified that compared levels of TREM2 in the brains of patients with AD and controls ( Supplementary Materials Table 6 ). Two identified an increase of TREM2 in AD, 61 , 106 whereas one reported no difference relative to control 76 and one reported opposing results for qPCR and western analysis. 107 …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Four papers were identified that compared levels of TREM2 in the brains of patients with AD and controls ( Supplementary Materials Table 6 ). Two identified an increase of TREM2 in AD, 61 , 106 whereas one reported no difference relative to control 76 and one reported opposing results for qPCR and western analysis. 107 …”
Section: Resultsmentioning
confidence: 95%
“…Both papers that examined the temporal cortex identified an increase in TREM2, either for the protein, 61 , 106 staining intensity by immunohistochemistry 61 or gene expression. 106 Roussos et al 107 examined the impact of R47H genotype on TREM2 mRNA and protein in the superior temporal gyrus. They also reported higher TREM2 gene expression in AD R47H carriers relative to controls and no difference in TREM2 between AD noncarriers and control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we were able to follow the time dependence from begin of the monitoring. Values for both peritoneal and renal Na and P removal showed great intra- and interindividual variability which is commonly encountered in studies examining solute clearance in PD [20, 21]. We addressed this by using a mixed model with time as independent variable and taking into account each replicate values of a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding peritoneal dialysis, its removal is highly dependent of RKF with very low peritoneal clearance [45,46]. However, clearance of cystatin C was reported to be higher during continuous ambulatory peritoneal dialysis (CAPD) when compared with continuous cycling peritoneal dialysis (CCPD), but still the proportion of peritoneal clearance was only around 3-20% of total Cys C clearance [47].…”
Section: Cystatin Cmentioning
confidence: 99%